2018
DOI: 10.5812/jjnpp.67178
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Nasturtium Officinale (Watercress) Ethanol Extract and Vitamin E on Vancomycin-Induced Nephrotoxicity in Rats

Abstract: Background: Vancomycin (VCM) is an important antibiotic that is active against gram-positive cocci, and its nephrotoxicity remain as a major problem in clinical use. Objectives: This study was designed to investigate the effect of Nasturtium officinale hydro-alcoholic extract (NOE) and vitamin E aganist VCM-induced nephrotoxicity in adult male wistar rats. Methods: A total of 36 animals were randomly divided into 6 equal groups (n = 6) including 1, control group; 2, VCM group; 3, VCM + NOE (250 mg/kg) group; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…In our investigation, the mean of BUN in the supplementation individuals decreased compared to baseline levels, and this change was significant compared with the placebo group. In accordance with our investigation, Karami et al showed that administering EENO attenuated vancomycin-induced nephrotoxicity and reduced BUN levels due to vancomycin injection [ 16 ]. Another study by Shahani et al represented that the EENO extract inhibited the gentamicin-induced toxicity in rats and decreased BUN and inflammatory parameters in rats [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our investigation, the mean of BUN in the supplementation individuals decreased compared to baseline levels, and this change was significant compared with the placebo group. In accordance with our investigation, Karami et al showed that administering EENO attenuated vancomycin-induced nephrotoxicity and reduced BUN levels due to vancomycin injection [ 16 ]. Another study by Shahani et al represented that the EENO extract inhibited the gentamicin-induced toxicity in rats and decreased BUN and inflammatory parameters in rats [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…In traditional Iranian medicine, watercress is used to treat diabetes, bronchitis, wound, tuberculosis, influenza, and asthma [ 10 ]. Previous studies have demonstrated antioxidant [ 11 13 ], anti-inflammatory [ 14 ], hepatoprotective [ 15 ], nephroprotective [ 16 ], and anti-hyperlipidemia [ 17 ] properties of the watercress in vitro and in vivo conditions. Furthermore, it has been reported that watercress supplementation can decrease DNA injury to lymphocytes and modify blood antioxidant status in healthy subjects [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This plant’s leaves are commonly eaten in fresh form in salads, soups, and other recipes and are very rich in vitamins, particularly vitamin C ( 14 ). The anticancer, hepatoprotective, nephroprotective, and antihyperlipidemic properties of watercress have been demonstrated in both in vitro and in vivo conditions ( 15 16 ). Also, some studies have shown that watercress exhibits significant antioxidant and anti-inflammatory activities in experimental conditions ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The histopathological changes of liver induced by acetaminophen were considerably reversed following treatment by aqueous and total extract of N. officinale. Karami et al [67] investigated the protective activity of the methanolic extract of N. officinale against gamma-radiation-induced hepatotoxicity along with histopathological changes. The results revealed that pre-treatment with 100 mg/kg body weight of plant extract per day for 15 days and 2 h before γ-radiation significantly lowered incidence of inflammation (portal and periportal inflammation).…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Karami et al [79] inspected the potential of hydroalcoholic extract of N. officinale (NOE) and Vitamin E against vancomycin (VCM)-induced nephrotoxicity against adult Wistar male rats. VCM significantly escalated serum creatinine and urea levels, MDA levels, kidney weight/100 mg weight of body, as well as reduced creatinine clearance.…”
Section: Nephroprotective Activitymentioning
confidence: 99%